Torso. (Berlin : Quadro-Verlag, 1982)
Fonds Suzan Daniel (FSD)
Verschijnt vanaf (1983)1 bij Torso-Verlag
Periodiciteit : maandelijks
Redactie : Postfach 30 13 45, Lützowstraße 105 1000 Berlin 30
Duits
Periodiek